2014
DOI: 10.1039/c4cc00868e
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired synthesis of rare and unnatural carbohydrates and cyclitols through strain driven epimerization

Abstract: We report a bio-inspired, strain driven epimerization of trans-ketals to cis-ketals through an enolate intermediate. Swern oxidation of a hydroxyl group adjacent to a trans-ketal effects both oxidation and its epimerization to cis-ketal. This novel and general strategy allows inversion of up to three contiguous stereocenters and has been illustrated by the synthesis of several unnatural/rare isomers of carbohydrates/cyclitols from their naturally abundant isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…16 It is noteworthy that the Swern oxidation of 8 leads to epimerization of the transketal to cis-ketal 14; hence, it cannot be used for this transformation. 17 The reduction of enone 9 using K-selectride afforded alcohol 10 with the desired stereochemistry in 90% yield over two steps. The bulky hydride donor ensured hydride delivery from opposite side of the protected O-2.…”
Section: Resultsmentioning
confidence: 99%
“…16 It is noteworthy that the Swern oxidation of 8 leads to epimerization of the transketal to cis-ketal 14; hence, it cannot be used for this transformation. 17 The reduction of enone 9 using K-selectride afforded alcohol 10 with the desired stereochemistry in 90% yield over two steps. The bulky hydride donor ensured hydride delivery from opposite side of the protected O-2.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Nitrocyclitols belong to the large family of cyclitols (also found as carbocyclic polyols or carbasugars). [15][16][17][18] They are essentially found as synthetic precursors of aminocyclitols. [19,20] However natural nitrosugars moieties do exist and are derived from aminosugars via an oxidation step.…”
Section: Introductionmentioning
confidence: 99%
“…[17,23,24] Consequently, there have been continuous efforts in the last decade to prepare natural cyclitols and aminocyclitols as well as analogues with enhanced or more selective biological profiles in order to study in depth the influence of this moiety on their specific receptors. [15][16][17][18][25][26][27] Few years ago, we have reported that nitrocyclitols can be efficiently prepared by a one-pot multi-step chemoenzymatic synthesis, consisting of an aldol reaction catalyzed by an aldolase and an intramolecular spontaneous Henry reaction as key steps (scheme 1). On the one hand, starting from several nitrobutanals fructose-1,6-bisphosphate aldolase (FBA) [28][29][30] and fructose-6-phosphate aldolase (FSA) [20,31] have led to nitroaldols with 3S,4R (becoming 2S,3R in the final cyclitol) defined configurations.…”
Section: Introductionmentioning
confidence: 99%
“…xylosides at C2, C3, and C4 by performing a Swern oxidation [319][320] or by oxidation with Dess-Martin periodinane 88,321 . Another method for epimerization is the transformation of the hydroxyl group into a better leaving group followed by an SN2 reaction.…”
Section: Modificationsmentioning
confidence: 99%